Kajian Pengawasan Auditor Inspektorat Daerah Terhadap Efektifitas Pelaksanaan Tugas Dan Fungsi Aparatur Pada Perangkat Daerah - Novrabella Clarashinta Pakasi (Gorontalo Management Research, 2019)
Tulisan ini akan mengkaji tentang pengawasan  auditor Inspektorat Daerah terhadap efektifitas pelaksanaan tugas dan fungsi aparatur pada Perangkat Daerah Pemerintah Provinsi Sulawesi Utara. Penelitian ini dilakukan di Inspektorat Daerah Provinsi Sulawesi Utara. Inti dari tulisan ini bertujuan untuk mengetahui bagaimana pengawasan  auditor Inspektorat Daerah terhadap efektifitas pelaksanaan tugas dan fungsi aparatur pada Perangkat Daerah Pemerintah Provinsi Sulawesi Utara. Teknik dan prosedur pengumpulan data melalui wawancara mendalam kepada sejumlah informan berkaitan dengan pengawasan  auditor terhadap efektifitas pelaksanaan tugas dan fungsi aparatur. Informan penelitian yaitu Auditor dan pengawas penyelenggaraan pemerintahan daerah (P2UPD) pada Inspektorat Daerah Provinsi Sulawesi Utara. Hasil penelitian ini menunjukkan bahwa pengawasan  auditor inspektorat daerah terhadap efektifitas pelaksanaan tugas dan fungsi aparatur pada perangkat daerah Pemerintah Provinsi Sulawesi Utara sudah cukup maksimal. Inspektorat Daerah Provinsi Sulawesi Utara sudah mampu mendeteksi kelemahan-kelemahan pelaksanaan tugas dan fungsi aparatur pada perangkat daerah secara dini, sehingga perangkat daerah dapat memperbaiki kelemahan-kelemahan tersebut berdasarkan saran-saran dari Inspektorat Daerah. This paper will examine the supervision of Regional Inspectorate auditors on the effectiveness of the implementation of the duties and functions of apparatus in the Regional Apparatus of the North Sulawesi Provincial Government. This research was conducted at the Regional Inspectorate of North Sulawesi Province. The core of this paper aims to find out how the supervision of the Regional Inspectorate auditors will be effective in carrying out the duties and functions of the apparatus in the Regional Apparatus of the North Sulawesi Provincial Government. The techniques and procedures for collecting data through in-depth interviews with a number of informants related to the auditor's supervision of the effectiveness of the implementation of the duties and functions of the apparatus. The research informants were the Auditor and supervisor of regional government implementation (P2UPD) at the Regional Inspectorate of North Sulawesi Province. The results of this study indicate that the supervision of the regional inspectorate auditor on the effectiveness of the implementation of the duties and functions of the apparatus in the regional apparatus of the North Sulawesi Provincial Government is quite maximal. The North Sulawesi Provincial Inspectorate has been able to detect weaknesses in the implementation of tasks and functions of the apparatus in the regional apparatus at an early stage, so that regional authorities can correct these weaknesses based on suggestions from the Regional Inspectorate.